αB-Crystallin Alleviates Endotoxin-Induced Retinal Inflammation and Inhibits Microglial Activation and Autophagy - Wang, Fangyu; Jiang, Zhaoxin; Lou, Bingsheng; Duan, Fang; Qiu, Suo; Cheng, Zhixing; Ma, Xinqi; Yang, Yao; Lin, Xiaofeng (Frontiers in Immunology, 2021)
αB-Crystallin, a member of the small heat shock protein (sHSP) family, plays an immunomodulatory and neuroprotective role by inhibiting microglial activation in several diseases. However, its effect on endotoxin-induced uveitis (EIU) is unclear. Autophagy may be associated with microglial activation, and αB-crystallin is involved in the regulation of autophagy in some cells. The role of αB-crystallin in microglial autophagy is unknown. This study aimed to explore the role of αB-crystallin on retinal microglial autophagy, microglial activation, and neuroinflammation in both cultured BV2 cells and the EIU mouse model. Our results show that αB-crystallin reduced the release of typical proinflammatory cytokines at both the mRNA and protein level, inhibited microglial activation in morphology, and suppressed the expression of autophagy-related molecules and the number of autophagolysosomes in vitro. In the EIU mouse model, αB-crystallin treatment alleviated the release of ocular inflammatory cytokines and the representative signs of inflammation, reduced the apoptosis of ganglion cells, and rescued retinal inflammatory structural and functional damage, as evaluated by optical coherence tomographic and electroretinography. Taken together, these results indicate that αB-crystallin inhibits the activation of microglia and supresses microglial autophagy, ultimately reducing endotoxin-induced neuroinflammation. In conclusion, αB-crystallin provides a novel and promising option for affecting microglial autophagy and alleviating symptoms of ocular inflammatory diseases